Confesiones - Ferrari, Gualberto (France, 2011)
For many years, Gustavo S. worked as a secret agent for Battalion 601, an intelligence agency in the Argentine army. Many years later, he found himself being arrested and facing accusations of criminal activity on the part of Battalion 601. This is the story of his fight for truth and transparency in a nation whose history is still covered in a shroud of uncertainty.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films